Responding to Health Crises: A Review of Emergency Preparedness and Healthcare Resilience - Alrashidi, Shafi Bani; Alrasheedi, Reem Khaleef; Alosayfir, Eid Salah Eid; Albreet, Nadih Abdulrahman; Alshahrani, Nouf Saad Mohammed; Albugami, Fawziah Faleh; Alanazi, Maha Abd Fanosh; Alqahtani, Abdullah Mohammed Abdullah (Journal of Posthumanism, 2024)
Health crises—ranging from pandemics and natural disasters to armed conflicts—pose significant threats to the stability and functionality of healthcare systems. This review examines the frameworks, strategies, and structural capacities that shape effective emergency preparedness and healthcare system resilience. Drawing on global case studies and recent literature, the paper explores how countries prepare for, respond to, and recover from health emergencies. It highlights critical factors such as inter-agency coordination, workforce readiness, infrastructure adaptability, digital innovation, and community engagement. Evidence suggests that integrated planning, sustained investment, and responsive governance are essential for strengthening health system resilience. The findings underscore the need for healthcare systems to transition from reactive crisis management to proactive and adaptive preparedness strategies. This review provides practical insights for policymakers, health administrators, and emergency planners aiming to enhance systemic resilience in the face of evolving global health threats.